Genetic Gains in Yield and Yield Related Traits under Drought Stress and Favorable Environments in a Maize Population Improved Using Marker Assisted Recurrent Selection - Bankole, Folusho; Menkir, Abebe; Olaoye, Gbadebo; Crossa, Jose; Hearne, Sarah; Unachukwu, Nnanna; Gedil, Melaku (Frontiers in Plant Science, 2017)
Marker assisted recurrent selection (MARS) aims at increasing the frequency of favourable marker alleles in a population prior to inbred line extraction. This approach was used to improve drought tolerance and grain yield in a biparental cross of two elite drought tolerant lines. The testcrosses of randomly selected 50 S1 lines from each of the three selection cycles (C0, C1, C2) of the MARS population, parental testcrosses and the cross between the two parents (F1) were evaluated under drought stress (DS) and well watered (WW) well as under rainfed conditions to determine genetic gains in grain yield and other agronomic traits. Also, the S1 lines derived from each selection types were genotyped with single nucleotide polymorphism (SNP) markers. Testcrosses derived from C2 produced significantly higher grain field under DS than those derived from C0 with a relative genetic gain of 7% per cycle. Also, the testcrosses of S1 lines from C2 showed an average genetic gain of 1% per cycle under WW condition and 7% per cycle under rainfed condition. Molecular analysis revealed an increase in the frequency of favourable marker alleles from 0.510 at C0 to 0.515 at C2, while the effective number of alleles (Ne) per locus decreased from C0 (1.93) to C2 (1.87). Our results underscore the effectiveness of MARS for improvement of grain yield under DS and favourable irrigated and rainfed conditions.